2017
DOI: 10.1080/10903127.2017.1332127
|View full text |Cite
|
Sign up to set email alerts
|

Patient Characteristics and Temporal Trends in Police Transport of Blunt Trauma Patients: A Multicenter Retrospective Cohort Study

Abstract: Background Police transport (PT) of penetrating trauma patients has the potential to decrease prehospital times for patients with life-threatening hemorrhage and is part of official policy in Philadelphia, Pennsylvania. We hypothesized that rates of PT of bluntly injured patients have increased over the past decade. Methods We used Pennsylvania Trauma Outcomes Study registry data from 2006–15 to identify bluntly injured adult patients transported to all 8 trauma centers in Philadelphia. PT was compared to am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 16 publications
1
26
0
Order By: Relevance
“…broader Social and Systemic Impact beyond the potential for police scoop and run to enhance survival, there are opportunities for other beneficial outcomes to be yielded by police hospital transport. A majority of police-transported patients in the united States are young black men (Kaufman et al 2017;Wandling et al 2016). They are often injured in communities with historically strained police-citizen relationships (Johnson 2004;brunson and Miller 2006;Isom 2016;Desmond, Papachristos, and Kirk 2016).…”
Section: Is Police Hospital Transport Effective?mentioning
confidence: 99%
See 2 more Smart Citations
“…broader Social and Systemic Impact beyond the potential for police scoop and run to enhance survival, there are opportunities for other beneficial outcomes to be yielded by police hospital transport. A majority of police-transported patients in the united States are young black men (Kaufman et al 2017;Wandling et al 2016). They are often injured in communities with historically strained police-citizen relationships (Johnson 2004;brunson and Miller 2006;Isom 2016;Desmond, Papachristos, and Kirk 2016).…”
Section: Is Police Hospital Transport Effective?mentioning
confidence: 99%
“…Patients who could particularly benefit from eMS, for example, include blunt-force motor vehicle crash injuries, spinal cord injuries, and burns (Holena, Jacoby, and reilly 2017). An evaluation of nearly thirty thousand trauma patients in Philadelphia from 2006 to 2015 identified that a small minority (1.2 percent) of blunt injury patients arrived at trauma centers via police, but that of these, more than 60 percent may have benefited from prehospital procedures like supplemental oxygen and spine stabilization (Kaufman et al 2017). Public controversy over whether police can appropriately implement triage for transport in Philadelphia was highlighted in the wake of an Amtrak train derailment in 2015, which caused more than two hundred injuries and eight deaths (Whelan 2016).…”
Section: Is Police Hospital Transport Effective?mentioning
confidence: 99%
See 1 more Smart Citation
“…For the majority of the 20 th century, peripheral intravenous (PIV) access complemented by venous cut-down served as the standard of care for vascular access after injury (1, 2). These intravascular access techniques were supplanted by the development of percutaneous central venous catheters (CVC) in 1952 (2, 3). Despite its development in the early 1920s(4) and subsequent use in World War II, until recently intraosseous (IO) access was uncommonly utilized for vascular access in civilian populations of adult patients.…”
Section: Introductionmentioning
confidence: 99%
“…Philadelphia is unlike many cities in the US in that police have been allowed to transport victims of penetrating injury to trauma centers since 1996 (Philadelphia Police Department Directive 3.14, available online at http://www.phillypolice.com/accountability). Increasing numbers of penetrating trauma patients are being transported by police (8) and in such cases, patients typically arrive with limited pre-notification and no vascular access (3) (9). We noted that in patients arriving in extremis, establishing successful vascular access was challenging and often resulted in multiple failed attempts with potential delays to lifesaving therapies.…”
Section: Introductionmentioning
confidence: 99%